(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
The purpose of this paper is to substantiate the arrangement of workings that supply cooled air to the faces based on an assessment of changes in the energy state of the rock mass under the influence of mining operations. The theoretical studies were carried out based on a systematic analysis of the fundamental equations of the classical theory of thermodynamics, taking into account experimental data on rock physics and geomechanical processes occurring during mining operations. This purpose was achieved by comparing the energy state (enthalpy) of rocks in the mass intact by mining operations and the mass formed in these rocks after coal seam extraction. The authors proposed the idea of transporting refrigerant in the form of cooled air through the workings arranged in the displaced rocks behind the longwall, which are relieved of rock pressure, degassed and cooled. This makes it possible to significantly reduce cold losses on the way to the miners’ workplaces. The results of theoretical preliminary calculations confirm that the enthalpy of displaced rocks in the mined-out longwall space remains virtually unchanged regardless of the depth of mining. This confirms the validity of the idea of choosing the arrangement of the workings to save cold. The linear nature of the increase in the ratio of rock enthalpy in intact and cooled rock masses during the deepening of mining operations has been established, which proves the efficiency and prospects of the proposed method for large depths. A variant of coal seam preparation and mining is proposed to ensure the saving of the cold resource by arranging workings in displaced and cooled rocks.